2007
DOI: 10.1016/j.ejcts.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative micronutrient supplementation in lung surgery. A prospective randomized trial of oral supplementation of combined α-ketoglutaric acid and 5-hydroxymethylfurfural

Abstract: Simple oral supplementation using a combination of alpha-KG and 5-HMF of preoperative micronutrition may therefore be one further step in a multimodality approach of fast-track surgery programs also in lung surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…We found that the addition of ␣KG rescued the negative effect of high levels of CO 2 on cell proliferation. This is in agreement with the suggestion of ␣KG as a potential pharmacological agent to improve some mitochondrial pathological disorders such as those with ATP synthase deficiency (45) and in patients undergoing lung resection to decrease oxidative stress (46).…”
Section: Discussionsupporting
confidence: 91%
“…We found that the addition of ␣KG rescued the negative effect of high levels of CO 2 on cell proliferation. This is in agreement with the suggestion of ␣KG as a potential pharmacological agent to improve some mitochondrial pathological disorders such as those with ATP synthase deficiency (45) and in patients undergoing lung resection to decrease oxidative stress (46).…”
Section: Discussionsupporting
confidence: 91%
“…As the precursor of various amino acids and heterocyclic compounds [1,2], a-KG is used as a building block for synthesizing numerous important products, e.g. pharmaceutical agents, food additives and biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…When such effects could be confirmed after prolonged antioxidants supplementation, athletes or mountaineers would greatly benefit during acute altitude exposure. Matzi et al (2007) for instance demonstrated that the combined oral intake of α-KG compounded with 5-hydroxymethylfurfural (5-HMF) improved exercise capacity and reduced oxidative stress after lung surgery. In addition, 5-HMF has been shown to elicit protective properties against hypoxic injury (Li et al, 2011a and b) and on the vascular endothelium as demonstrated in human umbilical vein endothelial cells (HUVECs; Cao et al, 2013;Kim et al, 2011).…”
mentioning
confidence: 99%